A hybrid ruthenium alkynyl/zinc porphyrin "Cross Fourchée" with large cubic NLO properties1. Issue 17 (7th May 2015) - Merhi, Areej; Grelaud, Guillaume; Green, Katy A.; Minh, Ngo Hoang; Reynolds, Michael; Ledoux, Isabelle; Barlow, Adam; Wang, Genmiao; Cifuentes, Marie P.; Humphrey, Mark G.; Paul, Frédéric; Paul-Roth, Christine O.
<x xml:space="preserve">Abstract</x> An impressive cubic nonlinear optical coefficient (γTHG) was determined by third-harmonic generation at 1907 nm for a new star-shaped Zn(ii) porphyrin-based metallo-dendrimer containing twelve Ru(ii) centers.